Comparative evaluation on the thermal properties and stability of MWCNT nanofluid with conventional surfactants and ionic liquid - Bakthavatchalam, B. (Springer Science and Business Media B.V., 2022)
Conventional surfactants such as CTAB (cetrimonium bromide), SDS (sodium dodecyl sulphate), SDBS (sodium dodecyl sulphonate) are combined with nanofluids to improve the stability and thermal conductivity of nanofluids. These nanofluids are mainly used for heat transfer applications where heating and cooling are usual courses of action which result in surfactants producing foams and polluting the heat transfer media, affecting the total system performance. Besides, the common surfactant molecules that augment the thermal resistance between the nanoparticles and base fluid also affect the thermophysical properties of the nanofluid. In this paper, BmimCl (1-butyl-3-methylimidazolium chloride), a high purity ionic liquid (IL) with higher thermal stability was used to provide a comparative study on the stability and thermal properties with that of the conventional surfactants (CTAB, SDS, SDBS) on multiwalled carbon nanotubes (MWCNT)/propylene glycol (PG) nanofluid. The transient hot-wire based KD2-Pro and zeta potential results demonstrated that the inclusion of ionic liquid improved the thermal conductivity and stability of the formulated nanofluid. However, much like the conventional surfactants, the strong electrostatic repulsive force created by the ionic liquid was found to decrease when the temperature is increased. The outcome demonstrated the most extreme thermal conductivity upgrade of 33.7% at 303Â K and maximum dispersion stability of more than one month without any aggregation for the nanofluid containing ionic liquid. Â© 2020, AkadÃ©miai KiadÃ³, Budapest, Hungary.